Environmental implications of Universal Rural Road Access Program (URRAP) roads in Southwestern Ethiopia: The case of Jimma and Buno Bedelle zones - Hassen Negesso; Milkessa Edae (Multidisciplinary Journal for Education, Social and Technological Sciences)
Ethiopia has been undertaking numerous development programs and projects with the objective of taking a country to the middle-income countries in the near future. Universal Rural Road Access Program (URRAP) roads being constructed in Jimma and Bunno Bedele zones are among the projects in Ethiopia. Although these projects are assumed to bring desirable positive change, there are sometimes negative consequences on environmental issues. Accordingly, the objective of this study was to investigate the negative sides of these projects on environmental elements. Household survey with randomly selected household heads and in-depth interview, focus group discussion (FGD) and observation for purposively selected samples were used to collect relevant and required data. Thereby, data were analyzed quantitatively by using Statistical Package for Social Sciences (SPSS) and qualitatively through thematic method. The findings from the analyzed data show that rural roads being constructed by URRAP have both positive and negative impacts on plant species, bird species, reptile species, mammal’s species, amphibians’ species, soil, and climate. Finally, URRAP is in dilemma and needs an extensive and frequent supervision, monitoring, inclusive, interdisciplinary and sound strategies and policies by responsible bodies at all expected levels and contexts.